Simulation of energetic particle precipitation effects during the 2003–2004 Arctic winter. Issue 6 (8th June 2015) - Randall, C. E.; Harvey, V. L.; Holt, L. A.; Marsh, D. R.; Kinnison, D.; Funke, B.; Bernath, P. F.
Abstract: Energetic particle precipitation (EPP) during the 2003–2004 Arctic winter led to the production and subsequent transport of reactive odd nitrogen (NOx = NO + NO2 ) from the mesosphere and lower thermosphere (MLT) into the stratosphere. This caused NOx enhancements in the polar upper stratosphere in April 2004 that were unprecedented in the satellite record. Simulations of the 2003–2004 Arctic winter with the Whole Atmosphere Community Climate Model using Specified Dynamics (SD‐WACCM) are compared to satellite measurements to assess our understanding of the observed NOx enhancements. The comparisons show that SD‐WACCM clearly displays the descent of NOx produced by EPP but underestimates the enhancements by at least a factor of four. Comparisons with NO measurements in January and February indicate that SD‐WACCM most likely underestimates EPP‐induced NO production locally in the mesosphere because it does not include precipitation of high energy electrons. Comparisons with temperature measurements suggest that SD‐WACCM does not properly simulate recovery from a sudden stratospheric warming in early January, resulting in insufficient transport from the MLT into the stratosphere. Both of these factors probably contribute to the inability of SD‐WACCM to simulate the stratospheric NOx enhancements, although their relative importance is unclear. The work highlights the importance of considering the full spectrum of precipitating electrons in order to fully understand the impact of EPP on the atmosphere. It also suggests a need for high‐quality meteorological data and measurements of NOx throughout the polar winter MLT. Key Points: Energetic particle precipitation effects in Arctic winter 2003–2004 are modeled Transport of EPP‐NOx into the stratosphere is significantly underestimated Better knowledge of precipitating electrons and transport in MLT is needed